2022
DOI: 10.35945/gb.2022.13.007
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investments During the Coronomic Crisis and Armed Conflict in the Neighbourhood, Case of Georgia

Abstract: Paper provides an analysis of FDI challenges and their impact on the service sector of Georgia, under the covid-19 global pandemic, along with the armed conflict factor in Eastern Europe, between Ukraine and Russia. The article also discusses such issues as public debt, economic growth, employment, international rankings, trade, tourism and etc. Since the cases of different countries vary according to their economic structure, political reality, and even the readiness to overcome those newest and unprecedented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…While integration may bring about benefits, such as increased inbound tourism from other European countries and improved tourism infrastructure, it may also lead to increased competition and the potential loss of distinctiveness as a tourism destination. Moreover, the specific context of Georgia-its unique culture, history, and geopolitical location-will undoubtedly shape how these potential effects unfold (Kadagidze & Gamsakhurdia, 2022;Charaia, Lashkhi & Lashkhi, 2021;Charaia & Lashkhi, 2022;Papava & Charaia, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While integration may bring about benefits, such as increased inbound tourism from other European countries and improved tourism infrastructure, it may also lead to increased competition and the potential loss of distinctiveness as a tourism destination. Moreover, the specific context of Georgia-its unique culture, history, and geopolitical location-will undoubtedly shape how these potential effects unfold (Kadagidze & Gamsakhurdia, 2022;Charaia, Lashkhi & Lashkhi, 2021;Charaia & Lashkhi, 2022;Papava & Charaia, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, it is important to consider how these two phenomena, which represent global uncertainties (which are just about a year apart), are affecting the growth pattern of FDI inflows within ECs, particularly EECs, as well as to foreign countries. The study by Charaia et al (2022) found that the COVID-19 pandemic and the Russia-Ukraine crisis affect FDI flows into the services sector of Georgia. 14 Additionally, Tank and Ospanova (2022) project that the Russia-Ukraine crisis will lead to a reduction in FDI inflows.…”
Section: Theorymentioning
confidence: 99%
“…A mistake made in formulating economic policy during the coronomic crisis is to view the inflation caused by this crisis as a macroeconomic problem (Galbraith, 2021) when, in fact, inflation is mainly precipitated by the disruption of global supply chains (Charaia et al, 2022). To better understand the problem brought by the pandemic, current high inflation issues should be seen from the economics prism (Rodrik, 2022), i.e., economists must look deeper into the reasons of this particular inflation, whether it is an increase in demand, a fall in supply or the combination of different factors (Sachs, 2021).…”
Section: Supply-side Inflection Challengementioning
confidence: 99%